Genotypic distribution of hepatitis B virus in the Czech Republic: a possible association with modes of transmission and clinical outcome - Krekulova, Laura; Rehak, Vratislav; da Silva Filho, Hermes Pedreira; Zavoral, Miroslav; Riley, Lee W (European journal of gastroenterology & hepatology, 2003)
OBJECTIVE: The relationship between hepatitis B virus (HBV) genotype with disease or treatment outcome is beginning to be characterized. However, the link between genotype and disease transmission route has not been closely examined. We addressed this question in high-risk populations in Prague, Czech Republic. DESIGN: Patients with HBV infection were consecutively recruited into the study at an outpatient clinic between June 2000 and March 2001. Their serum samples were analysed for HBV S gene segments by polymerase chain reaction (PCR) test. The amplified product sequences were compared to those of known HBV genotypes. Patients were evaluated for other virus co-infections, and parenteral and sexual exposure histories. RESULTS: Of 57 consecutively recruited patients with evidence of HBV infection, 45 (79%) had PCR-detectable S gene sequences. Only genotypes A (n = 33; 73%) and D (n = 12; 27%) were found. There was no difference in the development of chronic infection between the two genotypes. Of nine patients co-infected with TTV, all were infected with HBV genotype A. There was a trend towards an association between number of lifetime sex partners and genotype A but not genotype D. CONCLUSIONS: In Prague, the number of HBV genotypes appears to be limited compared to other northern European countries, suggesting that the virus has recently spread in the high-risk populations. While a large proportion of HBV infections occur in intravenous drug users, a subset of HBV genotype A may be transmitted by sexual contact. An HBV subtype may influence modes of transmission of HBV.
Keywords: dospělí; Genotype; Female; Hepatitis B, Chronic; Adult; Substance Abuse, Intravenous; výsledek terapie; ženské pohlaví; DNA bakterií; Sexual Partners; Adolescent; sexuální partneři; DNA, Bacterial; lidé; genotyp; Treatment Outcome; intravenózní abúzus drog; chronická hepatitida B; Male; Aged; Czech Republic; Česká republika; lidé středního věku; senioři; mužské pohlaví; Hepatitis B virus; Middle Aged; mladiství; virus hepatitidy B; Humans